The transformations of poetic discourse and the formation of the symbol of women in modern poetry ( Read in Selected Models) - AL.Sammarraie,Ban Kadhim Makki (Tanjong Malim, 2022)
The transformations of poetic discourse and the formation of the symbol of women in modern poetry ( Read in Selected Models) by AL.Sammarraie,Ban Kadhim Makki